Risk factors, severity-related factors, and clinical outcomes of immune checkpoint inhibitor-associated pneumonitis in elderly patients with lung cancer - Ying Hu; Shuhua Chen; Yingying Lu; Lingjuan Yang (Frontiers in Oncology, 2026)
Objective This study aimed to investigate the clinical characteristics, risk factors, severity-related factors, and clinical outcomes of immune checkpoint inhibitor-associated pneumonitis (CIP) after immune checkpoint inhibitor (ICI) treatment in elderly patients with lung cancer, providing evidence for risk identification and nursing management during ICI therapy. Methods Clinical data from 206 elderly patients with lung cancer who received ICI therapy at the Second Affiliated Hospital of Naval Medical University between March 2024 and February 2026 were retrospectively collected. The incidence, onset time, and Common Terminology Criteria for Adverse Events (CTCAE) grade of CIP were recorded. Univariate and multivariable logistic regression analyses were performed to identify risk factors for CIP. Patients with CIP were classified into mild (grades 1–2) and moderate-to-severe (grade ≥3) groups. Clinical characteristics and outcomes were compared between the two groups. Firth penalized logistic regression was used to identify factors associated with CIP severity. Results Among the 206 patients, 33 developed CIP (16.0%). The median time to CIP onset was 58 (45–82) days, and 81.8% of cases occurred within 90 days after ICI initiation. Twenty-two patients (66.7%) had mild CIP and 11 (33.3%) had moderate-to-severe CIP. Multivariable logistic regression identified prior thoracic radiotherapy (OR = 3.34, 95% CI: 1.45–7.69), pulmonary comorbidity (OR = 2.94, 95% CI: 1.30–6.63), and combination therapy (OR = 3.68, 95% CI: 1.36–10.00) as independent risk factors for CIP. Firth penalized logistic regression showed that pulmonary comorbidity (OR = 8.44, 95% CI: 1.42–95.17, P = 0.017) and prior thoracic radiotherapy (OR = 5.56, 95% CI: 1.07–39.63, P = 0.041) were associated with moderate-to-severe CIP. Conclusion Most CIP cases occurred within the first 3 months after ICI treatment and were mild. Prior thoracic radiotherapy, pulmonary comorbidity, and combination therapy increased the risk of CIP, whereas pulmonary comorbidity and prior thoracic radiotherapy were associated with moderate-to-severe CIP in exploratory analysis. The above findings may provide a reference for the identification of patients with relevant risk factors, early monitoring, and nursing management during ICI treatment.